Spontaneous hematological remission of acute myeloid leukemia - Kaźmierczak, Maciej; Szczepaniak, Andrzej; Czyż, Anna; Rupa-Matysek, Joanna; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2014)
Spontaneous remission (SR) of acute myeloid leukemia (AML) in adults is observed very rarely. To date, about 100 cases have been presented in the literature. To our best knowledge, we describe the first adult Polish patient suffering from acute myelomonocytic leukemia (48, XY, +13, +21/46, XY), in whom after supportive therapy, including non-irradiated, non-leukocyte depleted red cell transfusions and low-dose corticosteroid, we observed resolution of the disease without cytogenetic remission. We suggest a potential transfusion-associated graft versus-host-diseases (TA-GVHD) and graft-versus leukemia (GVL) reaction which might lead to spontaneous hematological remission. However, we did not observe clinical symptoms of such reactions apart from a short episode of non-infectious diarrhea. Additionally, steroids were administered but their role in inducing SR, in our opinion, seems less probable. This 77-year-old man remained in SR for 7 months, when repeated analysis showed AML recurrence. He died due to septic shock 2.5 months later. Additionally, we present a review of the literature.